2011
DOI: 10.1371/journal.ppat.1002296
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sialyl Glycan Recognition in Host Tissue Tropism of the Avian Parasite Eimeria tenella

Abstract: Eimeria spp. are a highly successful group of intracellular protozoan parasites that develop within intestinal epithelial cells of poultry, causing coccidiosis. As a result of resistance against anticoccidial drugs and the expense of manufacturing live vaccines, it is necessary to understand the relationship between Eimeria and its host more deeply, with a view to developing recombinant vaccines. Eimeria possesses a family of microneme lectins (MICs) that contain microneme adhesive repeat regions (MARR). We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
86
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 47 publications
(77 reference statements)
4
86
0
2
Order By: Relevance
“…2B). The discovery of the MAR fold was accompanied by demonstration of sialic acid binding activity by TgMIC1-MARR and the contribution of sialyl recognition to host cell binding has been verified by inhibition of cell binding and invasion for both TgMIC1 and EtMIC3 in the presence of sialic acid competitor or neuraminidase [24,41]. Further structural analyses revealed that binding to the sialic acid saccharide is co-ordinated by hydrogen-bond and -stacking interactions respectively with conserved histidine and threonine residues within a HxT/HxS motif found in both type I and type II MARs (Figs.…”
Section: Sialic Acid Binding By Mar-domain Containing Proteins (Mcps)mentioning
confidence: 99%
See 1 more Smart Citation
“…2B). The discovery of the MAR fold was accompanied by demonstration of sialic acid binding activity by TgMIC1-MARR and the contribution of sialyl recognition to host cell binding has been verified by inhibition of cell binding and invasion for both TgMIC1 and EtMIC3 in the presence of sialic acid competitor or neuraminidase [24,41]. Further structural analyses revealed that binding to the sialic acid saccharide is co-ordinated by hydrogen-bond and -stacking interactions respectively with conserved histidine and threonine residues within a HxT/HxS motif found in both type I and type II MARs (Figs.…”
Section: Sialic Acid Binding By Mar-domain Containing Proteins (Mcps)mentioning
confidence: 99%
“…Carbohydrate microarrays provide a high-throughput screen to examine the binding of a protein to a vast array of oligosaccharide probes [44] allowing facile assessment of lectin binding to various different sialyl epitopes. Array experiments have given detailed insights into the respective sialyl-binding profiles of MCPs from T. gondii (TgMIC1-MARR, TgMIC13), N. caninum (NcMIC1-MARR) and E. tenella (EtMIC3-MAR1b and EtMIC3-MAR5, comprising EtMIC3-MAR1a, 1b, 1d and 1e) [24,41,42]. All of these MCPs bind wide ranges of probes, including common N-/O-glycan sequences, polysialic acids and gangliosides, and the data reveal both consistencies and subtle differences in binding, which when complemented by structural and sequence data encourages rationalization of the differing parasite The proteins contain arrays of Type I and Type II MAR domains; HxT/HxS motifs that co-ordinate binding to the sialic acid saccharide are indicated.…”
Section: Sialic Acid Binding By Mar-domain Containing Proteins (Mcps)mentioning
confidence: 99%
“…In a program with Steve Matthews's group, NGL microarray analyses have played a central role in studies of adhesive molecules, known as micronemal proteins (MICs), of Toxoplasma gondii and other apicomplexan parasites [22,23,24,25 ]. Information has been gleaned on the way that the apicomplexan parasites use their MICs to decipher and select carbohydrates of the host cells that they invade, with implications for host/tissue tropisms and pathobiology of infections, and designs of therapeutic molecules.…”
Section: Apicomplexan Parasitesmentioning
confidence: 99%
“…Among the proteins analyzed, a differing repertoire of sialyl ligands have been identified for MIC13 of T. gondii and MIC1 of Neospora caninum, also for MIC3 of Eimeria tenella (EtMIC3). Among the interesting findings is the lack of binding by EtMIC3 to Nglycolyl sialyl (NeuGc) sequences, suggesting an adaptation to the chicken host that lacks NeuGc [24]. A study of the 'apple'-domain-containing protein, TgMIC4, which is closely associated with TgMIC1, has revealed a broad spectrum of galactose-terminating oligosaccharide ligands (many of them asialo-forms of the TgMIC1 ligands) [25 ].…”
Section: Apicomplexan Parasitesmentioning
confidence: 99%
“…Plant N-linked glycans are classified as a high-mannose (Man)-type, with the structure of (Man) [5][6][7][8][9] N-acetylglucosamine (GlcNAc) 2 , a complex type, with a terminal GlcNAc or larger antennae that are β1,2-linked to the α1,6-or α1,3-Man of the core structure, and paucimannosidic-glycans, with an α1,3-fucose and/or a β1,2-xylose linked to the core pentasaccharide Man 3-2 GlcNAc 2 [15].…”
mentioning
confidence: 99%